RETENSI VANILIN DAN PERUBAHAN WARNA EKSTRAK PEKAT VANILI SELAMA PENYIMPANAN [Vanillin Retention and Color Changes of Concentrated Vanilla Extract During Storage] - Mira Sofyaningsih; Dr Sugiyono; Dwi Setyaningsih (Jurnal Teknologi dan Industri Pangan, 2011)
The purpose of this research was to observe vanillin retention and color changes during storage of concentrated vanilla extract at the low temperature (10°C), room temperature (30°C), and high temperature (55°C) for 49 days. The methodology of this research consisted of vanilla curing process, vanilla extraction, evaporation of vanilla extract, formulation of concentrated vanilla extract, and measuring the vanillin retention and color change.The best products of concentrated vanilla extract were made with formula containing 10 ml vanilla extract, 10 ml high fructose syrup (HFS) 55% and 3 ml of carboxyl methyl cellulose (CMC) solution 1% and that made with formula containing 10 ml vanilla extract, 15 ml glucose syrup 75°Brix and 3 ml of CMC solution 1%. The vanillin retention of both formulas had a trend to descrease. The pattern of vanillin retention and color change during storage of both formulas followed linear equations.Thetemperature and period of storage significantly affected the color of concentrated vanilla extract. Both formulas did not show any differences in vanillin retention and color during storage at refrigerator and room temperature.